Digital Marketing Strategy PT. Dewangga Travindo (Hajj and Umrah Agent) - Febriansyah, Rezki; Albab, Ulil; Abizar; Choiriyati, Sri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of the internet has brought about changes in the implementation of company marketing strategies. This aligns with the increasing interest in Umrah and Hajj in Indonesia. This research aims to understand how PT implements the digital marketing strategy. DEWANGGA TRAVINDO (Umrah and Hajj Agency). This research employs a qualitative descriptive approach. The data used consists of primary and secondary data. The research follows a qualitative descriptive approach. The results of this study indicate that the Umrah and Hajj Agency applies digital marketing steps as outlined by Thomas Joseph, encompassing the integration of critical elements of digital marketing such as content, SEO, social media, community web, mobile apps, search engines, and the effective utilization of CRM systems. Keywords: Strategy, Digital Marketing, Hajj & Umrah, Marketing Strategy.